2013
DOI: 10.1038/jhh.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of vascular smooth muscle-modulating microRNAs in human peripheral blood mononuclear cells: novel targets in essential hypertension

Abstract: Vascular smooth muscle cell (VSMC) phenotypic plasticity has a critical role in the pathophysiology of arterial remodeling in essential hypertension. MicroRNAs are emerging as potential biomarkers and therapeutic targets in cardiovascular disease. We assessed the expression levels of the microRNAs miR-143, miR-145, miR-21, miR-133 and miR-1, which are implicated in VSMC phenotypic modulation, in 60 patients with essential hypertension and 29 healthy individuals. All patients underwent 24-h ambulatory blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 37 publications
7
65
2
4
Order By: Relevance
“…We have previously reported that changes of microRNA levels in PBMCs of hypertensive patients are related to clinical parameters of the disease. (21,22) In the present study, we observed lower expression levels of miR-133a and miR-26b and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 12 higher levels of miR-1, miR-208b, miR-499 and miR-21 in hypertensive patients compared with healthy controls. This indicates a dysregulation of these microRNAs in peripheral blood mononuclear cells that possibly reflect cardiovascular changes that happen in response to disease in hypertensive patients.…”
Section: Discussionsupporting
confidence: 50%
“…We have previously reported that changes of microRNA levels in PBMCs of hypertensive patients are related to clinical parameters of the disease. (21,22) In the present study, we observed lower expression levels of miR-133a and miR-26b and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 12 higher levels of miR-1, miR-208b, miR-499 and miR-21 in hypertensive patients compared with healthy controls. This indicates a dysregulation of these microRNAs in peripheral blood mononuclear cells that possibly reflect cardiovascular changes that happen in response to disease in hypertensive patients.…”
Section: Discussionsupporting
confidence: 50%
“…[18,19] Amongst hypertensive individuals, miR-21, miR-143, and miR-145 negatively correlated with 24-hour ambulatory mean blood pressure, mean DBP and mean pulse pressure; miR-133 positively correlated with each of these measures. [18] Whilst associations for 24-hour mean blood pressure and mean DBP were not provided for miR-9 or miR-126, both correlated positively with mean pulse pressure. [19] Finally, miR-9 (but not miR-126) also correlated positively with left ventricular mass index.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 95%
“…This analysis implicated miR-181a in pathways associated with mitochondrial respiratory function, immunity and inflammation. [16] In a similar approach, the Vardas laboratory focussed on microRNAs linked to vascular smooth muscle modulation, [18] hypertrophy and endothelial dysfunction [19] in animal and tissue models.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 99%
“…15 MiR-1 has also been shown to participate in VSMC differentiation and phenotypic regulation. 16 Many studies have indicated that the knockdown of microRNA-30e (miR-30e) substantially represses lung cancer cell growth and tumorigenicity in a dose-dependent manner, 17 and antagonizes the morphological changes and the migratory and invasive characteristics of carcinoma cells. 18 Other studies have shown miR-30e involvement in cancer cell proliferation, migration and invasion.…”
Section: Vsmc Culture and Carotid Artery Balloon Injury In Ratsmentioning
confidence: 99%